2013
DOI: 10.1186/1752-1947-7-60
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of sporadic Burkitt’s lymphoma originating from the nasal septum: a case report

Abstract: IntroductionBurkitt’s lymphoma is a highly aggressive, small, non-cleaved B-cell non-Hodgkin's lymphoma. In the sporadic form of the disease that occurs in non-endemic areas around the world, most commonly in developed countries, patients usually present with an abdominal mass that frequently involves the ileocecal region of the bowel; ocular or orbital involvement is rare. Primary disease of the sinuses is uncommon and, to the best of our knowledge, that of the anterior septum has never been described. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Among extranodal head and neck presentations of sporadic Burkitt lymphoma, the nasopharynx and tonsils were the most common sites of occurrence in one large case series of American sporadic Burkitt lymphoma [ 3 ]. Other extranodal sites of involvement within the head and neck, which occur in less than 5% of patients with sporadic Burkitt lymphoma, include the nasopharynx, tonsils, palate, sinuses, nasal septum, and other facial bones [ 3 , 6 , 11 , 12 ]. This is the first reported case of primary Burkitt lymphoma of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Among extranodal head and neck presentations of sporadic Burkitt lymphoma, the nasopharynx and tonsils were the most common sites of occurrence in one large case series of American sporadic Burkitt lymphoma [ 3 ]. Other extranodal sites of involvement within the head and neck, which occur in less than 5% of patients with sporadic Burkitt lymphoma, include the nasopharynx, tonsils, palate, sinuses, nasal septum, and other facial bones [ 3 , 6 , 11 , 12 ]. This is the first reported case of primary Burkitt lymphoma of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of sporadic Burkitt lymphoma have been found in specific anatomic regions of the head such as those reported in Europe and Asia by Aslan and Patankar et al, respectively. 11,12 In some low-income health centers where minimally invasive surgical approaches or imaging guided biopsies are not always available, a rapid onset of action with more aggressive measures may clearly help a patient when an uncertain diagnosis arises, increasing the chances of survival and diminishing the risk for potential complications in late-onset treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The nose and paranasal sinuses, orbit(s), salivary glands are other sites in head and neck affected in descending order of frequency [11][12][13]. It generally affects the elderly, especially over the 6th decade of life, and the male: female ratio was 2:1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis suggested that lymphomas develop as a result of imbalanced immunoregulation, however in the great majority of malignant lymphomas; there is no overt immunologic abnormality. Malignant lymphomas are thought to arise in the oral cavity from components of the lymphoreticular system in the oral submucosa, usually Waldeyer's ring [9,11,12].…”
Section: Discussionmentioning
confidence: 99%